1997
DOI: 10.3801/iafss.fss.5-1153
|View full text |Cite
|
Sign up to set email alerts
|

Experimental And Numerical Study On The Behaviour Of A Steel Beam Under Ceiling Exposed To A Localized Fire

Abstract: Experimental heat transfer and temperature correlations are presented for a steel beam installed beneath a ceiling when exposed to a localized fire source. The heat flux distribution on every part of the beam is formulated as a function of flame length and the distance from the fire source. A specially written finite volume code CV-FEM, as well as the general-purpose finite element code ANSYS were used for the numerical simulation. Experimental values of heat fluxes were applied as boundary conditions for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…. Through comparison between the measured temperature against numerical calculations by using the heat flux correlation as the input, effectiveness of such numerical methods as Finite Element Method and Finite Difference Method as a tool for the fire safety assessment of such structures was also verified 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…. Through comparison between the measured temperature against numerical calculations by using the heat flux correlation as the input, effectiveness of such numerical methods as Finite Element Method and Finite Difference Method as a tool for the fire safety assessment of such structures was also verified 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Since the mechanical behavior of a structural member in fire is essentially controlled by its temperature field and mechanical Ceiling Figure 2 Experimental set up for a H-beam supporting an inert ceiling above a fire source constraint conditions, prediction of the temperature field is the key for the fire safety design of such structures. Early flame heat transfer measurements had already demonstrated a significant decay of flame heat flux in the upper half of a diffusion flame [29]. It implies if a building element is exposed to an intermittent flame, the thermal exposure should be much weaker than in a fully developed fire.…”
Section: Flame Heating By Localized Fires and Structural Fire Safety mentioning
confidence: 99%
“…The heat flux was measured on the downward and upward surfaces of the lower flange, on the web and on the lower surface of the upper flange of the beam at different horizontal distances from the stagnation point above the burner center. Temperature distribution on the beam surface was then calculated by Finite Element Method(FEM) and its combination with Finite Difference Method(CV-EM) with the measured heat flux as the boundary conditions and the surface convective heat transfer coefficient tuned as a, = 0.01kW/m2K from the flat ceiling test [29]. Figure 6 describes a comparison between thus simulated temperature profile and the measurement.…”
Section: Flame Heating By Localized Fires and Structural Fire Safety mentioning
confidence: 99%
“…As for the small-scale experiments, the heat flux distribution on every part of the beam has been represented as a function of the radial distance from the stagnation point (r) which is normalized by the flame tip length (L B or L C ), virtual source depth (z') and the height (H B or H C ). In this paper, the flame length (L B ,L C ) is calculated using the following equations [5].…”
Section: Comparison Between the Real -Scale And The Small-scale Expermentioning
confidence: 99%
“…Subsequently, we have formulated heat flux distribution on every part of the beam as a function of heat release rate and the distance from the fire source to the member. Then we made FEM, FDM and CFD-based numerical calculation models, and the validity of these models was verified by comparing the numerical temperature results with those obtained through the experiment [2,3,4,5,6]. From the results of these studies, we demonstrated the practical feasibility of our FEM and FDM-based mo dels to predict the temperature of members, also proposed a correction method of heat flux data, and developed a heat transfer coefficient for the experimental conditions.…”
Section: Introductionmentioning
confidence: 99%